Herminium gongshanense (Orchidaceae), a new species from China - Ye, Chao; Pandey, Tirtha Raj; Jin, Xiao-Hua (Phytotaxa, 2022)
A new species of Herminium (Orchidaceae) from China, H. gongshanense, is described and illustrated based on morphological characters and molecular systematics. Herminium gongshanense is rather isolated in Herminium and morphological similar to H. singulum but differs from it by having peduncle without bract-like leaflet, lip 3-lobed, lateral-lobes enclosing column, staminodes filamentous and half of column. Molecular phylogenetic results based on one nuclear marker (nrITS) and two plastid markers (matK and rbcL) indicated that H. gongshanense is sister to the remaining Herminium.